Molecular Characterization of Cryptosporidium Isolates Obtained from Human Immunodeficiency Virus-Infected Individuals Living in Switzerland, Kenya, and the United States - Morgan, Una (American Society for Microbiology, 2000)
A total of 22 Cryptosporidium isolates from human immunodeficiency virus-infected patients from Kenya, Switzerland, and the United States were examined at three genetic loci: the 18S ribosomal DNA, HSP-70, and acetyl coenzyme A synthetase genes. Four distinct Cryptosporidium genotypes were identified: (i) the Cryptosporidium parvum “human” genotype, (ii) the C. parvum “cattle” genotype, (iii) Cryptosporidium felis, and (iv) Cryptosporidium meleagridis. This is the first report of C. meleagridis in a human host. These results and those of others indicate that immunocompromised individuals are susceptible to a wide range of Cryptosporidium species and genotypes. Future studies are required to understand the full public health significance of Cryptosporidium genotypes and species in immunocompromised hosts.